THE INFLUENCE OF CONSUMER BEHAVIOR ON PURCHASE DECISIONS USING LIVE BROADCAST AND DIRECT MESSAGE (DM) FEATURES ON INSTAGRAM IN SAMARINDA CITY - Umi Zunaidah; Renita Kawuryan; Baynatul Rahma (RADJA PUBLIKA, 2024)
The aim of this study is to ascertain the impact of consumer behavior on consumer purchase decisions in online shops in Samarinda. This research discusses the causal relationship between variables using hypothesis testing. This study employs quantitative research methodologies. It utilized a sample size of 100 participants selected from the demographic of consumers that engage in online shopping on Instagram in Samarinda. The sampling technique employed was non-probability sampling method known as purposive sampling. The sample consists of individuals who have utilized the live broadcast feature and direct message (DM) in the Instagram application for a minimum of one year. The respondents are required to be between the ages of 18 and 45 and reside in Samarinda City. The research instrument is tested using several test methods, including validity test, reliability test, loading factor test, normality test, partial test (t test), simultaneous test (F test), and coefficient of determination test. The data analysis technique employs multiple linear regression analysis. The hypothesis testing utilizing SPPS version 26 software to streamline the data processing in this investigation. The results of this study indicate that the E-WOM variable has a positive and significant influence on purchasing decisions. The E-Promotion variable has a positive and significant influence on purchasing decisions. The Celebrity Endorser variable has a positive and significant influence on purchasing decisions. The trust variable has a positive and significant influence on purchasing decisions. This study also proves that the trust variable is the variable that has the most dominant influence on the purchasing decision variable.